(untitled) (Studia Prawnicze / The Legal Studies, 2014)
Omówienie zagadnienia dotyczącego uzasadnień orzeczeń sądowych jako formy realizacji prawa do sądu wymaga zwrócenia uwagi na przemiany zachodzące w procesie stosowania prawa, znajdujące odzwierciedlenie w sposobie uzasadniania rozstrzygnięć sądowych. Jednym z dających się zaobserwować w tej sferze zjawisk pozostaje przejście od sylogistycznego modelu stosowania prawa w kierunku modelu argumentacyjnego (dyskursywnego). Choć przyczyn tego procesu upatruje się przede wszystkim we właściwości języka prawnego (otwartości tekstowej, niedookreśloności pojęć, posługiwaniu się klauzulami generalnymi) oraz konieczności uczynienia z prawa elastycznego i efektywnego narzędzia regulacji nieustannie zmieniającej się rzeczywistości społecznej i gospodarczej, to powodów „popularności” modelu argumentacyjnego można doszukiwać się również w mnogości ośrodków tworzenia prawa i wzajemnym przenikaniu się systemów prawa krajowego, europejskiego i międzynarodowego oraz panujących tam – stopniowalnych ze swej istoty – zasad. The argumentative model of applying law helps to provide „the right for a better quality judgment“ for all citizens. A good example of such relations are decisions of administrative courts made after the Constitutional Tribunal issues a judgment which delays the date of an unconstitutional law becoming ineffective. In such situations, the court faces a conflict of values, i.e. the issue of unconstitutional relevant legal basis against the arguments behind the further applying, or refusing to apply, defective regulations in a given case. By resorting to the discursive paradigm, administrative courts can search for pro-constitutional solutions while taking into the position of a citizen in relations with administrative authorities. Although the argumentative model of arriving at solutions poses a challenge to the court, it seems to be better suited to requirements of ensuring the citizen‘s right to the administrative court and the standards of judiciary which follow that right, by making it easier to create an environment of a dialogue with the citizen and by creating a framework for sufficient guarantee of citizen‘s rights when faced by the public authorities.